Response of carnation (Dianthus caryophyllus) cv Master to water soluble fertilizer Sujala (19:19:19 NPK) - SINGH, ARVINDER; SHARMA, B P; GUPTA, Y C; DILTA, B S; LAISHRAM, NOMITA (The Indian Journal of Agricultural Sciences, 2026)
The present investigation was conducted at the Research Farm of The Department of Floriculture and Landscaping, Dr Yashwant Singh Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh during the year 2010 and 2011 to ascertain the response of carnation (Dianthus caryophyllus L.) cv Master to different doses and methods of application of water soluble fertilizer Sujala (19:19:19 NPK). The plants receiving treatment of 250 ppm N and K fertigation through urea and MOP + 250 ppm NPK foliar spray through Sujala once a week (T13) showed significant increase in the vegetative growth characteristics (plant height and stem length) as well as stimulated flowering parameters, viz. reduced the number of days to bud formation, first flowering, enhanced both the number of flowers per plant and flower size, reduced the number of days to harvesting stage, increasing the duration of flowering, weight of cut flower stem per plant and vase life in comparison to the recommended practices.